§ 1.

      7.
0 = f(x).

7.01.

 f(x) = x5 2x4 + 4x3 28x2 + 48x 16, x0 = 2;

7.02.

 f(x) = x4 2x3 + 5x2 28x + 36, x0 = 2;

7.03.

 f(x) = x5 3x4 x3 + 11x2 12x + 4, x0 = 1;

7.04.

 f(x) = x5 6x4 + 13x3 14x2 + 12x 8, x0 = 2;

7.05.

 f(x) = x4 + 8x3 x2 68x 84, x0 = 2;

7.06.

 f(x) = x5 6x4 + 13x3 14x2 + 12x 8, x0 = 2;

7.07.

 f(x) = x4 2x3 + 2x2 2x + 1, x0 = 1;

7.08.

 f(x) = x5 6x4 + 11x3 2x2 12x + 8, x0 = 2;

7.09.

 f(x) = x5 8x4 + 21x3 27x2 + 54x 81, x0 = 3;

7. 10.

 f(x) = x5 6x4 + 13x3 14x2 + 12x 8, x0 = 2;

7.11.

 f(x) = x6 4x5 8x4 + 62x2 + 96x 72, x0 = 2;

7.12.

 f(x) = x5 + 4x4 + 7x3 + 7x2 + 4x + 1, x0 = 1;

7.13.

 f(x) = 2x5 4x4 + x3 + x2 1, x0 = 1;

7.14.

 f(x) = 3x6 19x5 + 33x4 + 23x3 130x2 132x 40, x0 = 2;

7.15.

 f(x) = x6 + 6x5 21x4 + 7x3 x2 + 8 , x0 = 2;

7.16.

 f(x) = x6 6x5 + 12x4 5x3 18x2 + 36x 24, x0 = 2;

7.17.

 f(x) = 3x6 5x5 + 3x4 7x3 + 2x2 + 10x 6, x0 = 1;

7.18.

 f(x) = x6 + 6x5 12x4 + 5x3 + 18x2 36x + 24, x0 = 2;

7.19.

 f(x) = x6 9x5 + 27x4 39x3 + 108x2 32x + 324, x0 = 3;

7.20.

 f(x) = x6 5x5 + 5x4 + 6x3 + 4x2 40x + 32, x0 = 2;

7.21.

 f(x) = 2x6 20x5 + 66x4 67x3 + 9x2 189x + 351, x0 = 3;

7.22.

 f(x) = x5 17x4 + 94x3 190x2 + 161x 49, x0 = 1;

7.23.

 f(x) = x6 2x5 + 3x4 5x3 12x2 + 2x 1, x0 = 2;

7.24.

 f(x) = x6 6x5 + 12x4 5x3 18x2 + 36x 24, x0 = 2;

7.25.

 f(x) = 3x6 + 4x5 + 3x4 + x3 + 2x2 4x + 8, x0 = 2;

7.26.

 f(x) = x6 14x5 + 72x4 188x3 + 464x2 1344x + 1792, x0 = 4;

7.27.

 f(x) = x6 + 3x5 + 3x4 x3 6x2 6x 2, x0 = 1;

7.28.

 f(x) = x5 3x4 + 4x3 4x2 + 3x 1, x0 = 1;

7.29.

 f(x) = x5 + 2x4 3x3 + x2 + 4x 3, x0 = 1;

7.30.

 f(x) = 2x5 6x4 + 7x3 5x2 + 3x 1, x0 = 1;

7.31.

 f(x) = x6 2x4 + x3 4x2 8x + 4, x0 = 1;

7.32.

 f(x) = x5 12x4 + 49x3 76x2 + 48x 64, x0 = 4;

7.33.

 f(x) = x5 6x4 + 11x3 2x2 12x + 8, x0 = 2;

7.34.

 f(x) = 4x5 + 12x4 + x3 + 6x2 + 10x + 3, ;

7.35.

 f(x) = 3x5 18x4 + 41x3 54x2 + 60x 40, x0 = 2;

7.36.

 f(x) = x5 6x4 + 13x3 14x2 + 12x 8, x0 = 2.

\..\

                              Copyright © 2008-2009 ..   . .